2021
DOI: 10.37934/arfmts.80.2.8297
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Reaction Conditions for Hydroxypropylation of Saba Banana Starch

Abstract: The aim of this study was to investigate the effects of three reaction variables on the hydroxypropylation of Saba banana (Musa acuminata x Musa balbisiana) starch. The variables were reaction pH (10, 11 and 12), amount of propylene oxide (5, 10 and 15% v/w) and reaction temperature (35, 40 and 45 oC). Response Surface Methodology (RSM) using Central Composite Design was employed to explore the effects of these three variables on the Molar Substitution (MS), pasting properties, freeze-thaw stability and therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Waliszewski et al [ 35 ] have reported that the hydroxypropylated banana starches have a higher water-binding capacity, swelling power, and solubility, but lower pasting temperature and paste clarity compared to the native form. Lee et al [ 87 ] reported that the quantity of propylene oxide used in hydroxypropylation has the most pronounced effect on the Saba banana starch properties compared to pH and temperature reaction. The hydroxypropylated Saba banana starch was easier to cook, had higher freeze-thaw stability, more resistance to retrograde, and lower pasting properties and temperature.…”
Section: Modification Practicesmentioning
confidence: 99%
“…Waliszewski et al [ 35 ] have reported that the hydroxypropylated banana starches have a higher water-binding capacity, swelling power, and solubility, but lower pasting temperature and paste clarity compared to the native form. Lee et al [ 87 ] reported that the quantity of propylene oxide used in hydroxypropylation has the most pronounced effect on the Saba banana starch properties compared to pH and temperature reaction. The hydroxypropylated Saba banana starch was easier to cook, had higher freeze-thaw stability, more resistance to retrograde, and lower pasting properties and temperature.…”
Section: Modification Practicesmentioning
confidence: 99%